Prospects and modern vision of the discipline «Food and sanitary toxicology» - Kuzmin, Oleg; Kuts, Anatoly (My University, 2020)
The prospects and modern vision of the discipline «Food and sanitary toxicology» are evaluated. That allows applicants to develop a risk-oriented mindset, in which the issues of safety, preservation of health and work capacity are considered as the most important priorities in a person's life and activities; principles and methods of preventive nutrition for various categories of the population that come into contact with harmful substances in the course of their activities, or live in environmentally unfavorable conditions. Оцінено перспективи та сучасне бачення дисципліни «Харчова та санітарна токсикологія». Що дозволяє здобувачам розвинути ризико-орієнтоване мислення, при якому питання безпечності, збереження здоров’я та працездатності розглядаються як найважливіші пріоритети в житті та діяльності людини; принципів і методів профілактичного харчування для різних категорій населення, які контактують зі шкідливими речовинами в процесі їх діяльності, або проживають в екологічно несприятливих умовах.
Keywords: кафедра технології ресторанної і аюрведичної продукції; кафедра біотехнології продуктів бродіння і виноробства; food toxicology; sanitary toxicology; safety; harmful substances; харчова токсикологія; санітарна токсикологія; безпечність; шкідливі речовини